Wear and corrosion behavior of tungsten carbide based coating on carbon steel - Ahmad, Noor Aqilah; Kamdi, Zakiah; Mohd Tobi, Abdul Latif (UTHM, 2018)
High velocity oxy-fuel (HVOF) coating techniques are employed mainly to improve the service life of engineering components, which is exposed to wear, erosion, corrosion or combination of both; wear and corrosion. The aim of this study is to investigate the wear and corrosion behavior of tungsten carbide 10 wt.% nickel (WC-10Ni) and tungsten carbide 12 wt.% w cobalt (WC-12Co) coating deposited onto medium carbon steel (Cast steel BS 3100 GR A3) blade. The blade was used to stir the mixture of sulfuric acid (H2SO4) with ilmenite to produce titanium dioxide (TiO2) pigments. The microstructures of both coatings before and after wear and corrosion testing were evaluated by using scanning electron microscope (SEM). Vickers microhardness testing was used to examine the coatings hardness. The three-body wear test with wet condition using silicon carbide (SiC) slurry was used to investigate the wear behavior for both coating. The experiment was based on weight loss of the sample and Archard’s law to determine the wear rate of the coating. In addition, the three-electrode electrochemical test was used to investigate the corrosion behavior of the coatings. The mixture of H2SO4 and ilmenite used as an electrolyte of the test. It is found that the wear rate will increase with increasing of the weight loss. This is consistent with decreases of the volume fraction loss and hardness of the coating. After corrosion test, it can be observed that the existence of the crack and porosity on the coating increasing the corrosion behavior of coating. With high volume fraction and hardness, WC-12Co shows higher wear resistance compared to WC-10Ni. However, the value of corrosion rate for both coating has a slight difference due to better corrosion resistance of Ni binder itself.